Գրիգոր Բ. Վկայասերի նախաձեռնած թարգմանական շարժումը - Գևորգյան, Դավիթ (Մատենադարան)
In 1075/1076 Grigor Vkayaser (Martyrophil) started a prolific translational activity, trying to protect the Armenian Church from Byzantine encroachments, when a new geopolitical situation was created after the fall of the Bagratuni kingdom of Armenia. He enriched Armenian ecclesiastical literature, and with the help of his associates, established educational centers in Cilicia. For translating some writings, Grigor Vkayaser involved foreign translators generously paying them for their work. They translated the original Greek text verbatim into Armenian, and then the text was revised by an Armenian erudite. This method of translation requires a thorough study in order to gain a better understanding of the reasons for its use. В 1075/1076 г. Григор Вкаясер (Мартирофил) начал плодотворную переводческую деятельность, пытаясь защитить Армянскую церковь от византийских посягательств, когда после падения Армянского царства Багратидов создалась новая геополитическая ситуация. Он обогатил армянскую церковную книжность и с помощью своих единомышленников основал образовательныe центры в Киликии. Для перевода некоторых произведений Григор Вкаясер обращался к иностранным переводчикам, щедро оплачивая их труд. Они дословно переводили оригинальный греческий текст на армянский, после чего текст редактировали армянские вардапеты. Этот метод перевода требует тщательного изучения, дабы лучше понять причины его использования.
Keywords: Բանասիրություն